Misconceptions and the Acceptance of Evidence-based Nonsurgical Interventions for Knee Osteoarthritis. A Qualitative Study. Issue 9 (September 2019) - Bunzli, Samantha; O'Brien BHealthSci (hons), Penny; Ayton, Darshini; Dowsey, Michelle; Gunn, Jane; Choong, Peter; Manski-Nankervis, Jo-Anne
Abstract: Background: In contrast to best practice guidelines for knee osteoarthritis (OA), findings from several different healthcare settings have identified that nonsurgical treatments are underused and TKA is overused. Empirical evidence and qualitative observations suggest that patients' willingness to accept nonsurgical interventions for knee OA is low. A qualitative investigation of why patients may feel that such interventions are of little value may be an important step toward increasing their use in the treatment of knee OA Questions/purposes: This qualitative study was embedded in a larger study investigating patient-related factors (beliefs/attitudes toward knee OA and its treatment) and health-system related factors (access, referral pathways) known to influence patients' decisions to seek medical care. In this paper we focus on the patient-related factors with the aim of exploring why patients may feel that nonsurgical interventions are of little value in the treatment of knee OA. Methods: A cross-sectional qualitative study was conducted in a single tertiary hospital in Australia. Patients with endstage knee OA on the waiting list for TKA were approached during their preadmission appointment and invited to participate in one-to-one interviews. As prescribed by the qualitative approach, data collection and data analysis were performed in parallel and recruitment continued until the authors agreed that the themes identified would not change through interviews with subsequent participants, at which point, recruitment stopped. Thirty-seven patients were approached and 27 participated. Participants were 48% female; mean age was 67 years. Participants' beliefs about knee OA and its treatment were identified in the interview transcripts. Beliefs were grouped into five belief dimensions: identity beliefs (what knee OA is), causal beliefs (what causes knee OA), consequence beliefs (what the consequences of knee OA are), timeline beliefs (how long knee OA lasts) and treatment beliefs (how knee OA can be controlled). Results: All participants believed that their knee OA was "bone on bone" (identity beliefs) and most (> 14 participants) believed it was caused by "wear and tear" (causal beliefs). Most (> 14 participants) believed that loading the knee could further damage their "vulnerable" joint (consequence beliefs) and all believed that their pain would deteriorate over time (timeline beliefs). Many (>20 participants) believed that physiotherapy and exercise interventions would increase pain and could not replace lost knee cartilage. They preferred experimental and surgical treatments which they believed would replace lost cartilage and cure their knee pain (treatment beliefs). Conclusions: Common misconceptions about knee OA appear to influence patients' acceptance of nonsurgical, evidence-based treatments such as exercise and weight loss. Once the participants in this study had been "diagnosed" with "bone-on-bone" changes, many disregarded exercise-based interventions which they believed would damage their joint, in favor of alternative and experimental treatments, which they believed would regenerate lost knee cartilage. Future research involving larger, more representative samples are needed to understand how widespread these beliefs are and if/how they influence treatment decisions. In the meantime, clinicians seeking to encourage acceptance of nonsurgical interventions may consider exploring and targeting misconceptions that patients hold about the identity, causes, consequences, timeline, and treatment of knee OA. Level of Evidence: Level II, prognostic study.